STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM ANTISIPASI KRISIS AKHLAK PESERTA DIDIK PADA SMA NEGERI DI PALOPO - Syamsu Syamsu S (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This research aims to explore the implications of applied learning strategies of Islamic education teachers for anticipation moral crisis of students in high schools in Palopo. This type of research is quantitative descriptive model with ex post facto. The subject of this research is Islamic education teachers at six high schools in Palopo. Data collection techniques used observation, interviews, and questionnaires. Data analyze techniqueused statistic and qualitative methods. The results showed that: 1) Islamic education teachers in high schools in Palopo often apply various learning strategies; 2), The efforts of Islamic education teachers in high schools in Palopo often attempt to use morale education to anticipate morale crisis of students, to optimize teachers’ role and morale learning, 3) Learning strategies applied by Islamic education teachers are not significant to give implications towards the anticipated efforts of the high school students’ morale crisis in Palopo.